ANALISIS NILAI TAMBAH AGROINDUSTRI KERUPUK IKAN DI KOTA JAMBI - Elmida; Alamsyah, Zulkifli; Wahyuni, Ira (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
Indonesia is known as a country that produces various kinds of crackers, for example cassava crackers, fish crackers and so forth. Jambi City has done a lot of fish processing activities in a processing unit in Jambi City generally processing fish into crackers. In 2017 there were 128 cracker processing units with 184 workers, with the most fish cracker processors in Danau Teluk District as many as 57 units and Pelayangan District 64 processing units with a variety of processed fish based on river, lake, or aquaculture, to increase added value. This study aims to determine (i) find out the process of processing fish into fish crackers in Jambi City (ii) To analyze the added value obtained from processing fish crackers in Jambi City, (ii) To analyze any factors affecting the added value of crackers fish. know the process of fish cracker processing, know the value of fish cracker value added can be done by using the formula contained in the hayami method, knowing the factors that influence the value using multiple linear regression analysis methods, the results of the study indicate the area of ​​research is the center of fish crackers typical of Seberang City , the production process is carried out twice a week, the production capacity of 6.57 per production with raw materials used cork fish and lamb fish as raw material for fish crackers added value of Rp.24,917 in agro-industry is quite high and the regression results obtained that the factor factors affecting the value added ratio of raw materials and fish species in agro-industry together have a significant effect on value added.